1990
DOI: 10.1210/jcem-71-5-1083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormonal Status on Bone Density in Adolescent Girls*

Abstract: Few data are available on bone density in late adolescence. We studied factors affecting peak bone density in females. Forty-three white girls, aged 13-20 yr, were studied. Integrated estrogen exposure over the pubertal years was obtained by a score based on physiological events known to reflect circulation estrogen levels. The subjects were selected to provide great variation in estrogen exposure. Bone mineral density (BMD) was measured by single photon absorptiometry (midradius) and dual photon absorptiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 34 publications
3
60
1
1
Order By: Relevance
“…This close relationship between bone mass and anthropometric variables had already been identified in early studies by Mazess and Cameron (22) and was later confirmed in studies performed on bone from the appendicular bone structures (19,(23)(24)(25)(26)(27)(28) and from the lumbar spine (10,11,15,16,29,30).…”
Section: Discussionsupporting
confidence: 68%
“…This close relationship between bone mass and anthropometric variables had already been identified in early studies by Mazess and Cameron (22) and was later confirmed in studies performed on bone from the appendicular bone structures (19,(23)(24)(25)(26)(27)(28) and from the lumbar spine (10,11,15,16,29,30).…”
Section: Discussionsupporting
confidence: 68%
“…The results of the current study reflect results reported in human studies. Delayed menarche has been correlated with low bone mass (BMD) [10][11][12] and an increased incidence of stress fractures [13]. Delayed pubertal onset in humans has been found to delay skeletal maturation, however, this was compensated by a late acceleration of linear growth [22].…”
Section: Discussionmentioning
confidence: 99%
“…Peak bone mineral accrual rate occurs at puberty [8], with an accrual of 26% of adult total bone mineral within 2 years [9]. However, a delay in the timing of puberty is one factor among many that correlate with low bone mass in young women [10][11][12]. Warren et al (2002) [13] found the age of menarche to be more correlated to stress fracture occurrence than bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 99%
“…Como a taxa de perda óssea em mulheres hipoestrogênicas é maior nos cinco a seis anos que se seguem à redução dos níveis de estrogênio endó-geno, pode haver somente uma breve janela de oportunidade para iniciar o tratamento para prevenir uma perda óssea irreversível. Na atleta adolescente, uma má nutrição e uma condição hipoestrogênica pode resultar em uma redução da formação do banco ósseo durante os anos críticos da consolidação do esqueleto 23,[130][131][132][133][134] . Uma questão importante é se a baixa DMO hipoestrogêni-ca pode ser tratada ou revertida até atingir uma DMO normal.…”
Section: Osteoporoseunclassified